2018
DOI: 10.1194/jlr.m082149
|View full text |Cite
|
Sign up to set email alerts
|

PIP4K2A regulates intracellular cholesterol transport through modulating PI(4,5)P2 homeostasis

Abstract: The transport of LDL-derived cholesterol from lysosomes to peroxisomes is mediated by membrane contacts, which are facilitated by the lysosomal protein synaptotagmin VII and the peroxisomal lipid phosphatidylinositol 4, 5-bisphosphate (PI(4,5)P 2 ). Here, we used RNA interference to search for regulators of PI(4,5)P 2 and to study the effects of altered PI(4,5)P 2 homeostasis on cholesterol transport. We found that knockdown of phosphatidylinositol 5-phosphate 4-kinase type-2 alpha (PIP4K2A) reduced peroxisoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 28 publications
(28 reference statements)
5
52
0
Order By: Relevance
“…Briefly, fractionation studies show that PtdIns represents ∼5% of the total phospholipid content of the peroxisomes (Hardeman et al, 1990) as well as suggest, relative to other inositol-containing lipids, that the levels of PtdIns4P, PtdIns(3,5)P 2 , and PtdIns(4,5)P 2 are enriched in peroxisomal membranes (Jeynov et al, 2006). The potential for a specific enrichment of PPIn lipids is supported by recent reports describing the interaction of PtdIns(4,5)P 2 present on the peroxisome surface with the lysosomal protein synaptotagmin VII to establish contact sites between lysosomes and peroxisomes (Chu et al, 2015; Hu et al, 2018). More studies will be needed to define the role of PtdIns and PPIn species in these compartments.…”
Section: Discussionmentioning
confidence: 81%
“…Briefly, fractionation studies show that PtdIns represents ∼5% of the total phospholipid content of the peroxisomes (Hardeman et al, 1990) as well as suggest, relative to other inositol-containing lipids, that the levels of PtdIns4P, PtdIns(3,5)P 2 , and PtdIns(4,5)P 2 are enriched in peroxisomal membranes (Jeynov et al, 2006). The potential for a specific enrichment of PPIn lipids is supported by recent reports describing the interaction of PtdIns(4,5)P 2 present on the peroxisome surface with the lysosomal protein synaptotagmin VII to establish contact sites between lysosomes and peroxisomes (Chu et al, 2015; Hu et al, 2018). More studies will be needed to define the role of PtdIns and PPIn species in these compartments.…”
Section: Discussionmentioning
confidence: 81%
“…(Hardeman et al, 1990), and more recent measurements suggest that, among PPIn species, the levels of PI4P, PI(3,5)P 2 , and PI(4,5)P 2 are enriched in peroxisomal membranes (Jeynov et al, 2006). The potential for a specific role for PPIn lipids in peroxisomes is supported by recent reports describing interaction between PI(4,5)P 2 present on the peroxisome surface and the lysosomal protein synaptotagmin VII, which is important for establishing functionally relevant contact sites between lysosomes and peroxisomes (Chu et al, 2015;Hu et al, 2018). Undoubtedly, additional studies are needed to better define the role of PI and PPIn species within these diverse compartments.…”
Section: Discussionmentioning
confidence: 92%
“…In 2015, the Bao-Liang Song research group demonstrated that cholesterol transport is abnormal in ALD fibroblasts and in the Abcd1 mouse model for ALD as well as in other peroxisomal disorders. Low-density lipoprotein (LDL)-derived cholesterol was transported from the lysosome to the peroxisome in a manner that depended upon lysosomal synaptotagmin VII binding to the peroxisomal lipid phosphatidylinositol 4, 5-bisphosphate [PI(4,5)P 2 ] on the peroxisomal membrane (Chu et al, 2015;Hu et al, 2018;Islinger, Voelkl, Fahimi, & Schrader, 2018;Jin, Strunk, & Weisman, 2015;Luo, Jiang, Yang, & Song, 2018;Luo, Liao, Xiao, & Song, 2017;Stefan et al, 2017). While these findings were initially called into question by van Veldhoven et al in a letter to the editor (van Veldhoven, Baes, & Fransen, 2015), correctly identifying an error in Chu et al's method, a recent follow-up publication (Xiao et al, 2019) validates the initial Chu et al (2015) findings.…”
Section: Cholesterol Transport In Aldmentioning
confidence: 99%